2017
DOI: 10.1111/muan.12130
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Native Digital Voice: Technology and Inclusivity in Museums

Abstract: The exclusion of Native Americans from their own cultural heritage is a persistent problem in twenty‐first museums. Although in recent decades museums have greatly expanded their programs and institutional frameworks to be more inclusive, experimental projects remain vital to creating new bridges between American museums and Native Americans. In 2010 and 2011, an innovative pilot program titled the “Native American Museum and Technology Workshop” was hosted at the Denver Museum of Nature & Science. The two‐wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The second is a commitment by both parties to collaborate on a collection management policy and to share decision making about access to digital and other information. This MOU is consistent with emerging museum and Indigenous community practices acknowledging Indigenous perspectives on collection management and affirming Indigenous peoples' rights over their heritage resources (60,61). The evolving relationship between the UM and the Penobscot Nation, underscored by the MOU, is a model for other tribes and institutions both within and outside of Maine and will drive curatorial improvements for the UM collections.…”
Section: The Intersection Of Legacy Collections and Indigenous Stakehsupporting
confidence: 66%
“…The second is a commitment by both parties to collaborate on a collection management policy and to share decision making about access to digital and other information. This MOU is consistent with emerging museum and Indigenous community practices acknowledging Indigenous perspectives on collection management and affirming Indigenous peoples' rights over their heritage resources (60,61). The evolving relationship between the UM and the Penobscot Nation, underscored by the MOU, is a model for other tribes and institutions both within and outside of Maine and will drive curatorial improvements for the UM collections.…”
Section: The Intersection Of Legacy Collections and Indigenous Stakehsupporting
confidence: 66%
“…In effect, digital circulation has served to further “decontextualize and reappropriate” images of Indigenous peoples. Importantly, Guiliano and Heitman ( 2019 :13) observe that digital humanities scholars remain separate from Indigenous communities, scholars and scholarship, and this situation impacts upon capacity building and development of digital method and practice that prioritizes Indigenous data governance of digital heritage (Pohawpatchoko et al 2017 ; Grey and Kuokkanen 2020 ; Shiri et al 2021 ).…”
Section: Indigenous Data Governance and Cultural Protocol For Digital...mentioning
confidence: 99%
“…In addition to vocation experts, youth can also serve as brokers of community cultural knowledge. For example, in a different study, 10 Native American youth helped inform and develop a local museum's web features (see Table 4) (Pohawpatchoko, Colwell, Powell, & Lassos, 2017). Pohawpatchoko et al (2017) later found that students who attended workshops on applying aspects of ethnocomputing showed stronger connections to the museum and increased web skills.…”
Section: Narrative Synthesis Of the Systematic Reviewmentioning
confidence: 99%
“…For example, in a different study, 10 Native American youth helped inform and develop a local museum's web features (see Table 4) (Pohawpatchoko, Colwell, Powell, & Lassos, 2017). Pohawpatchoko et al (2017) later found that students who attended workshops on applying aspects of ethnocomputing showed stronger connections to the museum and increased web skills. The strength of building connections also extends to pre-service teachers learning how to administer CRE in technology education.…”
Section: Narrative Synthesis Of the Systematic Reviewmentioning
confidence: 99%